Development of arbuscular mycorrhizal fungi in the presence of different patterns of Trifolium repens shoot flavonoids - Scervino, J.M. (2009)
We tested the effects of the flavonoid 3-methoxi-5,6,7,8-hydroxy-4'hydroxy flavone (NMHTV) isolated from shoots of non arbuscular mycorrhizal (AM) inoculated clover, and of the flavonoids 5,6,7,8-hydroxy-3-methoxy flavone (MH-1); 5,6,7,8-hydroxy-4'- hydroxy flavone (MH-2); and 5,7-hydroxy-3,4'-methoxy flavone (MH-3); isolated from AM clover (Trifolium repens) shoots, on spore germination, hyphal length, hyphal branches and the number of cluster of auxiliary cells or the number of secondary spores (Presymbiotic stage) and on the number of entry points and the percentage of AM colonized root of tomato (Lycopersicum esculentum) by the AM fungi Gigaspora rosea, Giaspora margarita, Glomus mosseae and Glomus intraradices (Symbiotic stage). Non significant effects of the flavonoids isolated from the shoot of mycorrhizal colonized clover on the presymbiotic and symbiotic stages of Gigaspora and Glomus endophytes were found. The flavonoid NMHTV isolated from non AM clover shoot, did not affect the percentage of germination of spores but significantly increased (P < 0.05) the other steps of the presymbiotic stage of Gi. margarita spores when 2 μM concentration was used. The symbiotic stage of Gi. margarita was also significantly increased when 2 μM of the flavonoid NMHTV was applied. This flavonoid had no effect on the presymbiotic development of G. mosseae, G. intraradices and Gi. rosea except when 8 μM concentration was used, which inhibited the hyphal length of Gi. rosea. These results suggest the possible implication of the flavonoid NMHTV in the susceptibility of tomato roots to the AM formation by Gi. margarita. The absence of stimulation of the AM presymbiotic and symbiotic stages in tomato by exogenous application of the newly synthesized flavonoids MH-1, MH-2, and MH-3, in clover shoots after AM colonization, indicated that the autorregulation of the AM symbiosis can be, at least partially, due to the disappearance of flavonoids in AM colonized plants that stimulated the AM symbiosis.